Studi Efektivitas Penambahan Bubuk Wortel dan Air Tebu Terhadap Kuat Tekan Beton Guna Mengurangi Dampak Pemanasan Global Akibat Produksi Semen - Yudistira Rizki Saputra; Fasyadilah Sufty Alaika; Vandra Andriansyah; Ananda Choirunisyah Dea Alquratu; Syafiq Baha Pridarta; Anggi Nidya Sari (Jurnal Talenta Sipil, 2023)
Cement production which continues to increase along with the high demand for concrete will greatly affect the global warming phenomenon. This is the background for specific research. As far as the literature review has been carried out, there have been findings in the form of carrots and sugar cane, but publications regarding this matter have not been very detailed, they are still carried out in the form of reports, both text and video. Therefore, there is a subjective thought that there is probably something that is still missing in the research. In view of this, the current research aims to determine the relationship between carrots and sugarcane juice in a concrete mixture on its compressive strength. Carrots are processed into powder without chemical additives and the sugar cane is extracted from pure water. The research was carried out on the basis of SNI and regulations that are still in effect with the number of test objects as many as 20 cylinders. In the end, the research facts show that the mix design calculation method by finding the average result of the three SNIs is not correct, because the 2 normal concrete test objects made did not reach the planned value. In addition, from the slump value test, it was found that there was only one and no modified concrete in accordance with the planned value. The results of the value of the compressive strength of concrete produced by all types of concrete specimens are that they do not exceed the planned compressive strength, which is 300 kg/m2.